Analisis Strategi Perbankan Syariah Dalam Menghadapi Konstruksi Ekonomi 5.0 Ditinjau Melalui Analisis SWOT (Studi Kasus PT. Bank Syariah Indonesia KCP Medan Padang Bulan) - Wardani, Aisyatul; Anggraini, Tuti; Harahap, Rahmat Daim (Journal of Student Development Informatics Management (JoSDIM), 2023)
Economic Construction 5.0 is a society that can solve various social challenges and problems by utilizing various innovations that were born in the era of the Industrial Revolution 4.0 such as Internet on Things (internet for everything), Artificial Intelligence (artificial intelligence), Big Data (large amounts of data) , and robots to improve the quality of human life. It is hoped that this research can add to the body of knowledge in the field of sharia banking, especially those related to the problem of sharia banking in facing economic construction 5.0 viewed through SWOT analysis, which can be used as reference material for further research that carries out similar research. The problem formulation of this research is how PT. BSI KCP Medan Padang Bulan and what obstacles are faced in facing Economic Construction 5.0 are reviewed through SWOT Analysis and what solutions or efforts are made to face these obstacles. This research uses a qualitative research model with a case study approach model, namely a research approach that tries to explore real life through detailed and in-depth data collection involving various sources of information, whether in the form of interviews, document observations or reports by describing the objects of the research case.